THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY, CUSTOMER SATISFACTION ON CUSTOMER LOYALTY - Lucinda Gratia Ambarita; Permata Ratu Sekarningsih; Yulimah Hening Swastika Lestari (Universitas Pelita Harapan, 2023)
The purpose of this study was to determine the effect of porduct quality, service, and custumer satisfaction on consumer loyalty. The method used is descriptive quantitative method. Data obtained by distributing questionnaires to the general public with 87 samples. The result showed taht product quality had no effect on consumer loyalty, service quality had a significant positive effect on consumer loyalty of the F test show that all the independent variables in this study simultaneously affect consumer loyalty by 84.4%.